Strategy to Increase Business Entity Compliance with BPJS Employment Contribution Payment: A Case Study of Contribution Receivables at the Sulawesi Maluku Regional Office - Octaviana Pongtuluran; Dikky Indrawan; Suhendi Suhendi (Sekolah Tinggi Agama Islam Kuningan, 2026)
Background: Employer non-compliance in BPJS Employment contribution payments poses a systemic risk to Indonesia's employment social security system, as persistent arrears threaten financial sustainability. The Sulawesi–Maluku Regional Office consistently ranks among the highest contributors to national receivables, recording IDR 158.84 billion in 2023 and IDR 157.27 billion in 2024 despite a declining number of delinquent entities. This divergence, particularly at the Makassar Branch Office, indicates a structural arrears problem that uniform compliance approaches have failed to address. Objective: This study aims to analyze the compliance conditions of Business Entities with contribution arrears at the Makassar Branch Office, identify key determinants of non-compliance, and formulate adaptive risk-based strategies to improve employer compliance in the Sulawesi–Maluku region. Methods: This study applies a quantitative approach using descriptive analysis of receivable trends (2022–2024) and binary logistic regression based on survey data from employers with outstanding contributions. Strategic priorities were formulated using SWOT analysis and the Analytic Hierarchy Process (AHP), supported by Focus Group Discussions (FGD). Results: Non-compliance was found to be structural and sectoral rather than random. Logistic regression analysis (n = 120) indicates that financial capacity is the only statistically significant determinant of non-compliance (OR = 3.47; p = 0.003), while perceptual and administrative factors show no significant effects. Conclusion: Non-compliance is primarily driven by financial constraints, highlighting the need for integrated, risk-based compliance strategies emphasizing governance strengthening and segmented billing to improve contribution recovery.